Coagulation removal of dissolved organic matter (DOM) in nanofiltration concentrate of biologically treated landfill leachate by ZrCl4: Performance, mechanism and coagulant recycling. (August 2022) - Hao, Weibo; Gao, Tong; Shi, Wansheng; Zhao, Mingxing; Huang, Zhenxing; Ren, Hongyan; Ruan, Wenquan
Abstract: Coagulation treatment is often applied for removing the residual refractory dissolved organic matter (DOM) in biologically treated landfill leachate nanofiltration concentrate (LLNC) before discharge or further desalination treatment. However, the DOM removal efficiency by traditional coagulant needs to be improved, and two problems including the coagulant loss and difficulty in disposal of coagulation sludge need to be resolved. Based on this practical demand, a new coagulant ZrCl4 was adopted for LLNC treatment for the first time. The results showed that, ZrCl4 was better than the traditional coagulants (FeCl3 and AlCl3 ) for DOM removal. Under the optimal condition of pH 6.0 and ZrCl4 dosage of 5.0 mM, the DOC content, UV254 and chromaticity of the LLNC reduced by 73.32%, 83.17% and 93.59%, respectively. All of the coagulants tested in this study could efficiently remove the hydrophobic and high molecular organics. There was an obvious difference between them for removal of hydrophobic, and small or medium molecular organics, and ZrCl4 was more effective. This might be due to the stronger negative charge neutralization capacity and larger floc size of ZrCl4, which was beneficial for DOM combination and adsorption. The loss of zirconium was only 2.11%, which was much lower than that of iron and aluminum. Furthermore, being recycled for 3 times after coagulant regeneration, the recovered zirconium coagulant showed no obvious difference with the original ZrCl4 for DOM removal, indicating the disposal problem of the produced coagulation sludge can be resolved. This study could provide a promising method for LLNC treatment. Graphical abstract: Image 1 Highlights: ZrCl4 was better for DOM removal from LLNC compared with FeCl3 and AlCl3 . ZrCl4 had a stronger negative charge neutralization and DOM adsorption capacity. ZrCl4 showed lower coagulant loss as only 2.11% of Zr resided in the effluent. The regenerated Zr from coagulation sludge can be reused for DOM removal from LLNC.